Extracellular vesicles in thalassemia: Mechanisms, implications, and therapeutic potential - Shahzad Ali Jiskani (Aspects of Molecular Medicine)
Thalassemia is one of the most common inherited disorders of erythrocytes, caused by abnormalities in the production of globin chains. The clinical spectrum of thalassemia is broad, ranging from severe and persistent anemia that necessitates consistent blood transfusions to mild, asymptomatic conditions. Key contributors to thalassemia complications, particularly, in patients with β-thalassemia major, are ineffective erythropoiesis and iron overload. These complications can lead to a variety of severe health issues, including chronic inflammation, organ dysfunction, thrombosis, vascular abnormalities, and systemic iron overload. Extracellular vesicles (EVs) are tiny membrane-bound particles secreted from the plasma membranes of various cells during activation and cell death. Research has indicated that EVs are involved in numerous physiological and pathological processes, including inflammatory responses, clot formation, and vascular injury. Recently, the role of EVs has garnered interest of their potential as biomarkers, providing diagnostic and prognostic value of various disorders. In the context of thalassemia, elevated levels of EVs have been observed, highlighting their significance in the disease's cellular activities. The current review aims to examine the role of EVs in the pathogenesis of thalassemia, their implications, and their potential clinical applications. By exploring the involvement of EVs in the inflammatory and vascular complications associated with thalassemia, this review provides insights into their potential as therapeutic targets and diagnostic tools, offering a new perspective on managing this complex and multifaceted disorder.